Design and Build a Manual Stirred Biodigester Using a 200 Liter Capacity Double Propeller Using Cow Manure and Rumen Raw Materials - Rahman, Edriza; Nadya Rizki, Ailsya; Supriadi, Eko; Rosalina, Rosalina (Riviera Publishing, 2024)
Processing organic waste into renewable energy is an effective solution to reduce environmental impact and meet energy needs. This research aims to design and build a manually stirred biodigester using a double propeller system with a capacity of 200 liters. This biodigester is designed to process cow manure waste and rumen as the main raw material, utilizing the abundant and not yet optimal biomass potential. A manual stirring system with two propellers is implemented to improve the mixing efficiency of the substrate, so as to maximize the production of biogas. Tests are carried out to evaluate the performance of the equipment, including the biogas production capacity, the quality of the methane gas produced, and the efficiency of the fermentation process. The results of the study show that the designed biodigester is able to produce biogas effectively with methane levels that meet energy use standards. Innovations in manual stirrers using double propellers have been proven to increase the homogeneity of the substrate, accelerate fermentation times, and increase the volume of gases produced. This biodigester has the potential to be applied on a household and community scale, supporting efforts to use sustainable renewable energy while reducing environmental pollution due to organic waste. This research is expected to be a reference in the development of biodigester technology that is efficient and easy to apply in various regions.